Cardiac resident macrophages: the emerging role in arrhythmogenesis - Zhao, Jiaqian; Liu, Jun; Zou, Ying; Li, Jianhong; Lei, Ming; Tan, Xiaoqiu; Chen, Tangting (Frontiers in Immunology, 2026)
Arrhythmia is a prevalent complication associated with various cardiovascular diseases. The onset of cardiac disease or injury can impair the normal function of cardiomyocytes, thereby precipitating arrhythmic events. Moreover, non-cardiomyocytes, including immune cells, may also play a contributory role in arrhythmogenesis. For instance, processes such as the infiltration of inflammatory cells that secrete pro-inflammatory mediators, fibroblast-to-myofibroblast transformation, and endothelial-to-mesenchymal transition have all been implicated in this process. Recent investigations have identified a distinct subset of resident macrophages within cardiac tissue that exhibit functional properties differing from those of bone marrow-derived macrophages. Cardiac tissue-resident macrophages (CRMs) are distinguished from bone marrow-derived macrophages by their developmental origin, transcriptomic profile, and functional traits. Beyond their canonical immune functions shared with bone marrow-derived macrophages, CRMs uniquely contribute to cardiac homeostasis by exerting direct electrophysiological modulation via ion channels and gap junctions. This constitutes a distinct mechanism underlying their role in arrhythmogenesis. Advanced methodologies, such as patch-clamp electrophysiology, high-throughput sequencing, and proteomic analyses in mammalian models, have revealed the complex electrophysiological interactions between CRMs and cardiomyocytes. While both CRMs and bone marrow-derived macrophages play roles in arrhythmia initiation and progression, existing reviews have primarily focused on bone marrow-derived macrophages. This review seeks to clarify the electrophysiological properties of CRMs and to delineate the specific mechanisms through which these cells contribute to arrhythmogenesis, thereby providing novel perspectives for the development of anti-arrhythmic therapeutic strategies.